Effects of selected herbal supplements in persons with type 2 diabetes - Rauniyar, Gajendra Prasad; Sinha, R; Pandey, DR; Chapagain, K; Maskey, R (Nepal Medical College Journal, 2020)
Diabetes mellitus is a metabolic abnormality leading to an increase in the plasma concentration of glucose and is a major cause of stroke and peripheral circulatory disorders. Momordica charantia (MC), commonly known as bitter gourd/Karela, and Trigonella foenum-graecum (TFG) (fenugreek/Methi) have several medicinal values like anti-diabetic, lipid-lowering property, anti-oxidant activity, anti-inflammatory, and anti-mutagenic activity. This is an open-label, four-parallel-group, prospective interventional clinical trial with a total number of 48 patients enrolled in the study and divided into four equal groups (12 in each group) viz; Group I (allopathic drug), Group II (allopathic drug and Karela (MC), Group III (allopathic drug and Methi (TFG) and Group IV (allopathic drug, methi, and karela). Blood sugar and lipid profile were measured at day 0 and day 90. One way ANOVA test was applied to find the significant difference between the groups and Tukey HSD post hoc test was applied for multiple comparisons among the four groups with probability p-value 0.05%. Multiple comparisons by post-hoc analysis between groups on day 90 showed a significant reduction of fasting blood sugar by 19.0% (p = 0.021), postprandial blood sugar by 35.0% (p= 0.001), total serum cholesterol by 14.0% (p= 0.000), serum triglyceride by 21.0% (p=0.000), and serum LDL cholesterol by 17.0% (p= 0.000)ingroup receiving Karela and fenugreek seeds supplementation. Whereas serum HDL cholesterol on the 90th day was higher in the group by 10.0% (p=0.015) receiving only fenugreek seeds as a supplementation. Fenugreek and karela, when given as a supplement, have a beneficial effect on blood sugar and lipid profile.